TINGKAT PARTISIPASI WANITA DALAM PEMBANGUNAN NON FISIK DI KEURAHAN KADIDI KECAMATAN PANCA RIJANG KABUPATEN SIDENRENG RAPPANG - Wahyuni Wahyuni; Andi Astinah Adnan; Kamaruddin Sellang (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2021)
This study aims to determine the participation of women in non-physical development in Kadidi Subdistrict, Panca Rijang Subdistrict, Sidenreng Rappang Regency and to determine the factors that influence women's participation in Kadidi Subdistrict, Panca Rijang Subdistrict, Sidenreng Rappang District.The population of this study was 411 women. A sample of 80 people. The sampling technique used is incidental sampling. This type of research is quantitative descriptive. Data collection techniques used were observation, questionnaire and literature study. The data analysis technique used is descriptive statistics and with the help of SPSS application version 21. The results showed that the Participation of Women in Kadidi Village with a percentage of 56.87% was in the unfavorable category. Non-Physical Development in Kadidi Urban Village with a percentage of 60% is in the unfavorable category. Based on the value of t arithmetic> t table or 6,415> 0,219 If the value of t arithmetic ≥ t table, then H0 is rejected and Ha is accepted, meaning Significant, If the value of t arithmetic ≤ t table, then H0 is accepted and Ha is rejected, meaning that is not Significant, then Ha accepted and H0 is rejected, it means that the Participation Rate of Women has a significant effect on Non-Physical Development in Kadidi Subdistrict, Panca Rijang Subdistrict, Sidenreng Rappang Regency with a contribution percentage of 54.5% being in the medium level or good kurag category. Factors Affecting Women's Participation: a. Internal Factors: 1) 59.2% participation, 2) Education 62.2%, 3) Income and income 64.6%. b. External Factors: 1) Leadership 65.2%, 2) Government Equipment / Facilities 60.6%. Based on the description above, it can be concluded that the factors that influence women's participation in the Kadidi Village are in the good category 62.36%.